A LINGUISTIC ANALYSIS OF DISCOURSE MARKERS IN ONLINE COMMUNICATION AMONG THE YOUTH - Rabbiyeva Ozoda Erkin qizi (Ustozlar uchun, 2025)
This study presents a linguistic analysis of discourse markers (DMs) in online communication among youth, focusing on their structural, functional, and social roles in digital discourse. Through the examination of 50 conversation threads collected from popular social media platforms, the research identifies the most commonly used discourse markers, such as like, so, well, I mean, and you know, and categorizes their functions into topic management, hesitation, emphasis, and politeness. The findings show that DMs play a crucial role in organizing discourse, managing turn-taking, and expressing interpersonal meaning, particularly in the absence of non-verbal cues. Additionally, youth exhibit a high degree of creativity and flexibility in their use of these markers, adapting them to fit the informal nature of online interactions. The study contributes to the understanding of digital language practices, highlighting how discourse markers function as both linguistic tools and social instruments in the construction of identity and group cohesion. Future research could explore the cross-platform use of DMs and the role of non-verbal markers in online communication.